Impact of conservation farming practices on Aspergillus population density, peanut aflatoxin level, and exposure risk in Zambia - Akello, Juliet; Alamu, Emmanuel Oladeji; Mwila, Chama Mebbyln; Kachapulula, Paul W.; Mukanga, Mweshi; Njapau, Henry; Chikoye, David; Ortega-Beltran, Alejandro; Bandyopadhyay, Ranajit (Frontiers in Sustainable Food Systems, 2024)
Aflatoxin contamination in peanuts (Arachis hypogaea L.) by aflatoxin-producing Aspergillus spp. is a serious problem worldwide affecting human health and restricting trade. Recently, conservation agriculture practices such as minimum tillage, crop rotation, soil surface cover, intercropping, and planting in basins alongside trees that enhance soil fertility, have been introduced in Zambia as tools to conserve soil moisture, increase peanut yield, and reduce the risk of aflatoxin contamination. However, a limited understanding exists of the impact of conservation agriculture on Aspergillus population densities in the soil and aflatoxin concentrations in crops grown under conservation agriculture. This study assessed the impact of conservation agriculture on (i) Aspergillus communities profile in soil cropped to peanuts, (ii) peanut aflatoxin contamination levels, and (iii) influences of the practices on liver cancer risks as a result of consuming peanuts grown in basins, peanuts grown in basins in farms having Gliricidia sepium trees (agroforestry), and peanuts grown on ridges (conventional tillage). Densities of Aspergillus spp. in soils ranged from 10 to 7,400 CFU/g (mean = 295 CFU/g). The densities differed among farming techniques (p = 0.0011) with conventional tillage (357 CFU/g) supporting higher densities than agroforestry (296 CFU/g) and peanuts grown in basins (230 CFU/g). Aspergillus communities were dominated by fungi with S morphology (55%; which is composed of several morphologically similar species), followed by A. parasiticus (34%), and the L morphotype of A. flavus (11%). Over 60% of the peanut samples were contaminated but there were no differences among farming techniques. Mean aflatoxin contents in peanuts were 110, 99, and 87, μg/kg for agroforestry, conventional tillage, and peanuts grown in basins, respectively. Probable daily aflatoxin intake ranged from 12.7 to 767.1 ng/kg body weight/d, depending on the age of consumers. The estimated liver cancer risk due to consumption of raw peanuts (0.334 to 20.128 cases/100,000 persons/year) was highest among children below 5 years and least for young adults. The results showed that growing peanuts in basins has the potential to reduce Aspergillus populations in soil. Possibly, planting in basins and agroforestry had minimal effect on water runoff and did not support sufficient moisture retention in the soil to reduce Aspergillus spp. densities and aflatoxin accumulation in the peanuts. Thus, more research is needed to improve the effectiveness of peanut cultivation in basins in shaping the Aspergillus species profiles for ultimately reducing aflatoxin in peanuts to safe levels. Given the high exposure of Zambia’s population, especially children, and that contaminated food is the major source of exposure, it is essential that appropriate technical, policy and institutional measures are promoted for aflatoxin mitigation in Zambia.